Students' Anxiety in Learning English as a Foreign Language. A Case from Indonesia - Erika Mae Lavarias Rodriguez (UNIB Press, 2022)
Although the study of students’ anxiety in learning English as a Foreign Language (EFL) in Indonesia has been conducted before, little attention is paid to whether gender or English level contributes more to the anxiety in learning. EFL students, particularly in Indonesia, find difficulty in learning the language because it has different rules from their own language. There is no such thing as gender-based personal pronouns or tenses in their verbs. It doesn’t have the plural form which is equivalent to adding “s” in English. In Bahasa Indonesia, how you spell it is how you pronounce it. While the spelling in English does not correspond with its pronunciation. 242 Grade 10 students, male and female in three different English levels (Levels 1,2, and 3) were included in the study. This study aims at researching the students’ anxiety level in terms of communication apprehension, fear of negative evaluation, and test-taking. Fear of negative evaluation shows the highest cause of students’ anxiety followed by test-taking and communication apprehension. Students in English Level 1 and 2 show a significant relationship to the level of anxiety, while students in Level 3 have no relationship between anxiety and that level. Gender has shown some significance but it is very weak. Between gender and English level, it shows that gender, though has weaker significance, contributes more to the anxiety compared to the English level. Further explication of each issue is discussed.